ETHICAL SENSITIVITY, PEMAHAMAN KODE ETIK PROFESI AKUNTAN DAN PENGARUHNYA TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI - Kusumawati, Nugrahini; Zahra, Surti; Septiani, Septiani (STAI Darul Qalam Tangerang, 2022)
Ethics As thought and moral considerations provide the basis for a person as well as a community in performing an action. Compliance with the code of ethics, like all standards in society is not, depends on the understanding or perception of the code of ethics. Ethical sensitivity also has an influence on the individual in making decisions about ethical actions. Data collection was done by using questionnaire. The number of samples in this study were 128 respondents and selected based on Slovin method and corrected by random sampling method. Namely the students of semester 4, 6, and 8 with the criteria of consideration can no longer switch majors and have taken accounting courses. The results of hypothesis testing show that the Ethical Sensitivity and Understanding of the Code of Professional Ethics of Accountants influence the Ethical Behavior of Accounting Students at Bina Bangsa University. Judging from the value of the F Test value F count 18.452> Ftable 3.069, with R square value of 22.8% while the rest of 0.722 percent is determined by other factors